Studi Mediasi Kepuasan Pelanggan Pada Industri Retail: Peran Kualitas Layanan dan Implikasinya terhadap Loyalitas Pelanggan - Ramadhan, Mohammad Nur Safri; Asnawi, Nur (IQTISHODUNA, 2020)
The purpose of this research is to determine the direct effect of retail service quality on customers' loyalty and satisfaction, the effect of customer satisfaction on their loyalty and how much customer satisfaction mediates retail service quality on customers' loyalty on Super Indo Bendungan Sutami customers, Malang. This research method uses comparative research with a quantitative approach. The sample used was 120 respondents with collected data by a questionnaire. The data analysis in this study used the Partial Least Square (PLS) method. The results of this research indicate that there is a direct effect of the retail service quality variable upon customers' loyalty and also on customer satisfaction which has a direct influence on customers of Super Indo Bendungan Sutami. Meanwhile, loyalty and can mediate the effect of retail service quality on customer loyalty.